2015
DOI: 10.1080/00223131.2015.1058196
|View full text |Cite
|
Sign up to set email alerts
|

Change of chemical states of niobium in the oxide layer of zirconium–niobium alloys with oxide growth

Abstract: The change of chemical states of niobium with oxide growth was examined in the oxide layers of Zr-2.5Nb around the first kinetic transition by the conversion electron yield -X-ray absorption near-edge structure measurements. The detailed depth profiles of niobium chemical states were obtained in both the pre-and the post-transition oxide layers of Zr-2.5Nb formed in water at 663 K for 40-280 d. The depth profiling revealed that the inner oxide layer remained protective to oxidizing species even though in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, experimental work [23,24] has consistently suggested Nb in ZrO 2 in fact occupies a range of states between 0 and 5+, with one X-ray absorption near edge structure (XANES) study by Froideval et al [25] unable to identify any 5+ Nb at all, thus casting doubt on the previous assumptions regarding the method by which Nb improves corrosion resistance and HPUF. Nb and Sn demonstrate some solid solubility in α-Zr and so an even distribution throughout the alloy is expected; this is an important point as the current investigation considers only single and paired defects isolated in a bulk oxide and thus an even distribution of dopants in the oxide layer is assumed.…”
Section: ••mentioning
confidence: 90%
“…However, experimental work [23,24] has consistently suggested Nb in ZrO 2 in fact occupies a range of states between 0 and 5+, with one X-ray absorption near edge structure (XANES) study by Froideval et al [25] unable to identify any 5+ Nb at all, thus casting doubt on the previous assumptions regarding the method by which Nb improves corrosion resistance and HPUF. Nb and Sn demonstrate some solid solubility in α-Zr and so an even distribution throughout the alloy is expected; this is an important point as the current investigation considers only single and paired defects isolated in a bulk oxide and thus an even distribution of dopants in the oxide layer is assumed.…”
Section: ••mentioning
confidence: 90%
“…The assumption that Nb exists only in the 5+ charge state in the oxide layer is supported by previous DFT simulation work [11]. However, several independent x-ray absorption near-edge spectroscopy (XANES) studies have identified oxidation states ranging from 5+ to 2+ (and also metallic Nb) in the oxide layer of Zr-Nb alloys [12,13,14,15,16]. Recently there has been some debate regarding the location of these lower charge state Nb ions (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…We have therefore tested near-edge spectra of Nb 2 O 5 (Nb 5+ ), NbO 2 (Nb 4+ ) and NbO (Nb 2+ ) for the modelling of the data. The XANES spectra of those Nb oxides show substantial differences at the edge and in the post-edge region (see, for example, Sakamoto et al, 2015), thus sensitively allowing their discrimination. It appears that by using the XANES of NbO, the fit errors and the uncertainties for the compositions are substantially smaller compared with the other oxides.…”
Section: Heat Treatments In Air At Low Pressuresmentioning
confidence: 99%